SULTHAN IN THE AL-QUR’AN - Andi Rama Dhani; Linda Susanti; Hasnah - (INNOVATIO: Journal for Religious Innovations Studies, 2022)
Allah SWT is the absolute ruler of the universe and its contents, but Allah SWT also gives a small portion of His power to His servants in different forms according to the needs of His servants. This foundation is the basis for researchers to carry out a study entitled "Sulthan” in the Qur'an. The main problem is what is the meaning of “Sulthan” in the Qur'an? How are the forms of “Sulthan” in the Qur'an? What is the function of the “Sulthan” in the Qur'an? This study uses a library research method, and for further discussion, the researcher uses the ‘maudhu'iy’, which uses various relevant commentary books. The researcher also completes this research with the hadiths of the Prophet Muhammad SAW, which the researcher quotes from the original source. Based on the research that the researchers conducted, it can be concluded that in the Qur'an, there are two meanings of “Sulthan”, namely, power and evidence, which are spread over 39 verses, and 27 surahs. The Qur'an also describes anyone who accepts the “Sulthan”, including Prophets, ordinary people, and demons/devils.“Sulthan” also has several functions: to have the correct beliefs, avoid punishment, and conquer opponents. As for the forms of “Sulthan” in the Qur'an that researchers can conclude are “isim” and “fi'il”, their function is to show the power of Allah and prove the weakness of the enemy of Allah SWT. Abstract: Allah SWT adalah penguasa mutlak alam semesta beserta isinya, namun Allah SWT juga memberikan sebagian kecil kekuasaan-Nya kepada para hamba-Nya dengan bentuk yang berbeda-beda sesuai kebutuhan hamba-Nya. Landasan inilah yang menjadi dasar peneliti untuk mengangkat sebuah penelitian yang berjudul “Sulthan dalam al-Qur’an”. Pokok permasalahannya adalah apa makna sulthan dalam al-Qur’an? Bagaimana bentuk-bentuk sulthan dalam al-Qur’an? Apa fungsi sulthan dalam al-Qur’an? Penelitian ini menggunakan metode riset kepustakaan (Library Research) dan sebagai pembahasan lebih lanjut peneliti menggunakan metode tafsir maudhu’iy yang menggunakan berbagai kitab tafsir yang relevan. Peneliti juga melengkapi penelitian ini dengan hadis-hadis Nabi SAW., yang peneliti kutip dari sumber aslinya. Berdasarkan penelitian yang peneliti lakukan, dapat ditarik kesimpulan bahwa di dalam al-Qur’an terdapat dua arti sulthan yaitu, kekuasaan dan bukti yang tersebar dalam 39 ayat, 27 surah. Al-Qur’an juga menggambarkan tentang siapa saja yang menerima sulthan, di antaranya Nabi/Rasul, manusia biasa dan setan/iblis. Sulthan juga memiliki beberapa fungsi, yaitu supaya berakidah yang benar, terhindar dari hukuman dan untuk menaklukkan lawan. Adapun Bentuk-bentuk sulthan didalam al-Qur’an yang dapat peneliti simpulkan adalah isim dan fi’il, Adapun fungsinya untuk menunjukkan kekuasaan Allah dan membuktikan kelemahan musuh Allah SWT. Kata Kunci: sulthan dan Al-Qur’an, ayat